Pengaruh Suplementasi Acacia mangium Willd pada Pennisetum purpureum terhadap Karakteristik Fermentasi dan Produksi Gas Metana in Vitro - B Santoso; B Tj Hariadi (Media Peternakan, 2007)
An in vitro study was conducted to determine the effect of Acacia mangium Willd supplementation to Pennisetum purpureum on fermentation characteristics, protozoal numbers, nutrients degradability and in vitro methane production. Treatments consisted of four composite substrates with P. purpureum and A. mangium Willd ratios at 100:0 (0%), 85:15 (15%), 70:30 (30%), and 55:45 (45%). Crude saponin and total tannin contents of A. mangium were 1.67% and 4.51%, respectively. Methane and gas productions decreased linearly (P < 0.01) in response to acacia levels. Addition of A. mangium at 15%, 30% and 45% decreased CH4 production by 16.2%, 26.8% and 61.1%, respectively as compared to the control. There were linear decreases in total VFA and acetate concentrations (P < 0.01), and propionate production (P < 0.05) in response to increase in acacia addition. Total protozoal populations increased linearly (P < 0.05) with added acacia. In vitro dry matter and organic matter degradabilities of substrate decreased linearly (P < 0.01) with acacia addition. It is concluded that methane production is not essentially associated with protozoal population. A. mangium has a potential use for mitigation of enteric methane production. Key words : Acacia mangium, methan, degradability, in vitro